Association of low fat mass with nontuberculous mycobacterial infection in patients with bronchiectasis - Lim, Sung Yoon; Lee, Yeon Joo; Park, Jong Sun; Cho, Young-Jae; Yoon, Ho Il; Lee, Choon-Taek; Lee, Jae Ho (Medicine (Baltimore), 2021)
The incidence of pulmonary nontuberculous mycobacterial (NTM) infection is high in patients with underlying lung disease such as bronchiectasis. Although previous studies have reported many risk factors contributing to the development of NTM-lung disease (LD), only a few reports on the relationship of the characteristics of patients, such as body mass index (BMI), skeletal mass, and fat mass, with NTM-LD have been published. We aimed to investigate the association between these parameters and NTM-LD in patients with bronchiectasis.A monocentric retrospective study in a university hospital was conducted over 4 years (2013-2016). Parameters including BMI, skeletal mass, and fat mass were measured using bioelectrical impedance analysis in noncystic fibrosis bronchiectasis patients. Patients were grouped by the presence or absence of NTM-LD, and the differences in BMI, skeletal mass, and fat mass between the 2 groups were compared. In the NTM-LD group, the progression of disease was also followed.Two hundred forty-five patients with bronchiectasis were enrolled in the study. One hundred six subjects (48%) had NTM-LD. These patients with NTM-LD were predominantly female, and had a significantly lower body weight (58.20 ± 8.84 vs 54.16 ± 8.99, P < .001), BMI (22.67 ± 3.04 vs 21.20 ± 2.59 kg/m2, P < .001), fat mass (16.19 ± 6.60 vs 14.23 ± 5.79, P = .013), and fat mass index (FMI; 6.79 ± 2.70 vs 5.57 ± 2.27 kg/m2, P < .001). Multivariate regression analysis showed that both female sex and lower FMI but not skeletal muscle index were independent risk factors for NTM-LD after adjusting for age, bronchiectasis severity index, and BMI (odds ratio 3.86 (1.99-7.78); 0.72 (0.63-0.82), P < .001, respectively).Our results suggest that lower FMI may contribute to susceptibility to NTM infection in patients with bronchiectasis, independent of age or its severity.